Urban Traffic Optimization with Real Time Intelligence Intersection Traffic Light System - Celik, Yuksel; Karadeniz, Alper Talha (Prof. Dr. Ismail SARITAS, 2018)
Traffic system is a complex system where a lot of smart components which include signals, vehicles, sensor and pedestrian have communication skills with together on local level and act in a particular manner on high level. Insufficient traffic light control system on intersections brings about unnecessary delays and waste of time, extremely oil firing of engine which run idle mode on lights and increasing greenhouse gas emission. Various systems have been developed in order to overcome these traffic problems. In this paper we proposed an Intelligence Traffic Light System. In this system, the traffic flow at intersections is optimized using instant traffic information. These are the primary developed methods for the traffic optimization systems: fixed time period systems of lighting where time is pre-determined, green wave lighting system and real time optimization system of traffic light. Real data of traffic has been gathered on Karabuk-Safranbolu route to test above systems for different data density. The results of these tests on data show that real time traffic light optimization systems get better results than fixed time period and green wave lighting systems.